The Role of Social Networks on Shrimp Fishers’ Access to Information and Gear in Rivers State - Komi, Gentle Wilson; Turyahabwe, Nelson; Isubikalu, Prossy; Amiye, Francis; Ibitoru, Aduabobo Hart (Journal of Agricultural Science and Technology, 2019)
Access to information and appropriate fishing gear is fundamental to the protection and conservation of the fisheries resources to guarantee sustainable livelihood of the fishers. Social networks in eight fishing settlements of Rivers State were purposively selected to assess the role of networks on access and use of information and gear among the shrimp fishers. The cross-sectional study used mixed methods to elicit data. Data obtained were subjected to content analysis and MAXQDA 2018 software to generate project maps showing information and fishing gear accessed and used. Results show that 24.8% (31) of respondents joined social network due to information sharing behavior of network members. Information was shared through one-on-one interactions, group meetings, fish buyers and phone calls. Out of the 96.8% (121) of respondents belonging to shrimp fishers’ network, 23.2% attended meetings for at least four times a month while 22.4% attended meetings for more than four times a month. Information shared bordered on price of shrimps, weather and tide, fishing grounds and traps, water level, timing of fishing and processing techniques. Respondents revealed that information shared in their networks was correct, adequate and timely. Fishing gear accessed and used proficiently was dragnet, cast net and beach seine. In all, the evidence from the interview responses suggests that networks play a key role in shrimp fishers’ access and use of information and fishing gear. Fishers are therefore, encouraged to be in one network or the other.
Keywords: Acquisition; Fisheries; Resources; Relationship; Niger Delta